Paraoxonase activity in healthy population of major ethnic groups - Abdullah, Nor Zamzila; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Nadiger, H. A (IIUM Press, International Islamic University Malaysia, 2017)
Ischaemic heart disease (IHD) is one of the leading causes of mortality globally with varying risk across different ethnic groups. Recent evidence has suggested a role for paraoxonase, an high density lipoprotein (HDL)associated enzyme in the prevention of atherosclerosis by inhibiting the oxidative modification of low density lipoprotein (LDL). Genetic polymorphism in paraoxonase 1 (PON1) gene (Arg192 and Gln192) with varying abilities to degrade oxidized LDL is being implicated as one of the risk factors for IHD. The distribution of PON1 polymorphic forms has been found to differ among the ethnic groups but conflicting results have been reported regarding their association with IHD risk. Indians, compared to other ethnic groups have been reported to carry a higher risk of IHD but the risk factors are still not well understood. In Malaysia, the existence of three separate ethnic groups with varying IHD incidence provides an ideal opportunity to carry out this study. The purpose of this study were to find out the PON1 activities, the phenotypic polymorphism of PON1 and the level of lipid profiles among the three major ethnic groups in Malaysia and their association with varying IHD risk among them. A prospective pilot study was carried out on a total number of 150 healthy volunteers who fulfilled the inclusion and exclusion criteria from September 2003 until July 2004.